Genetics of hereditary sensory and autonomic neuropathy (HSAN) - Tezel, Seden. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Hereditary Sensory Neuropathy (HSN), predominantly affects sensory nerves and is characterized by sensory loss in addition to muscle weakness, wasting and painless injuries. Autonomic symptoms are commonly associated with HSN, thus, it is also known as Hereditary Sensory and Autonomic Neuropathy (HSAN). A Turkish fam ily initially diagnosed with HSAN was investigated in this study to identify the gene responsible for the disorder. The consanguineous parents had three affected and one unaffected children suggesting autosomal recessive inheritance. Along with HSN, cough and gastroesophageal reflux (GER) have been reported as additional symptoms in fam ily. The disease was mapped previously to chromosome 3p22-24 in patients with this phenotype, however, the gene could not have been identified, yet. We have identified the causative candidate gene variants using whole exome sequencing (WES) data in the HSN family based on autosomal recessive, autosomal dominant, and X-linked inheri tance. WES data were further evaluated using HOMWES program for homozygosity mapping. The causative role of each variant was evaluated by segregation analysis. Unfortunately, these analyses gave inconclusive results with exclusion of 12 different candidate variants. A high rate of false positive results was observed when WES re sults were compared with that of direct sequencing. In last month of the study, upon hospitalization, the patient was re-diagnosed as cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS). The haplotype analysis showed the presence of CANVAS associated core haplotype among the affected members of the family. This finding indicated that repeat expansion of the (AAGGG)11 unit in RFC1 gene is responsible for the disorder in this family
Keywords: Genetic disorders.; Autonomic nervous system.